COVID-19 and the Medical Devices in India: Trade for a Resilient Health System - Ravinder Jha; Diwas Saun; Indrani Gupta (Indian Journal of Public Health)
Background: The medical devices industry plays a critical role in public health and requires attention in research and policy. The COVID-19 pandemic exposed a lack of resilience in areas of drugs and vaccines but also in medical products. Objectives: The study analyzes India’s strengths and weaknesses in the trade of medical devices and identifies specific devices where India can attain self-sufficiency and areas where trade is still beneficial. Materials and Methods: A set of critical products traded during the COVID-19 pandemic were identified from the World Integrated Trade Solution website at the 6-digit Harmonized System code level. A detailed analysis of exports and imports of medical products at disaggregated 8-digit codes was carried out. Results: During the pandemic, India had a trade surplus in some low-technology-based products such as suture needles, catheters, and cannulae along with X-ray apparatus and electrocardiographs among the medium-tech products. The imports of high-tech devices like in vitro diagnostics almost doubled to meet the surge in demand. The requirement of pulse oximeters, ventilators, and other monitoring devices jumped, and their imports reported an 800% increase from $134 million in 2019–2020 to $1162 million in 2021–2022. Most of India’s imports of medical devices come from the top five exporting countries, with the share of the USA and China at 39%–40%. Conclusion: There is a need to expand the manufacturing capacity of surgical instruments, consumables and disposables, apart from some high-tech products. The public health care facilities should procure domestically manufactured medical devices and trade with neighbouring countries to reduce import concentration must be prioritised.